Does the price puzzle exist in colombia? Empirical evidence and policy implications (2006)
The positive response of prices to an increase in interest rates or contractionary monetary policy has been documented by several empirical studies.2 According to monetarist as well as IS-LM models, an increase in interest rates or contractionary monetary policy reduces aggregate demand leading to a decrease in the Price level. As a result, this positive response of prices to positive interest rate shocks is perplexing and is referred to as the price puzzle. Sims (1992) set out to examine existing theory and evidence on the effects of monetary policy by using VAR methodology. He observed a positive response of the price level to contractionary monetary policy shocks, which was positive for many quarters. Sims speculated that the information set available to policy makers might include variables that are useful in forecasting future inflation that the econometrician has not yet considered. He believed the world commodity price to be one of these information variables and therefore proposed the inclusion of the commodity price to alleviate this problem. Consequently, he found that, when the VAR is extended to include a commodity price index, the puzzle almost disappears for the US